A QUANTITATIVE STUDY OF THE STIMULATION OF DNA SYNTHESIS IN LYMPH NODE CELL CULTURES BY ANTI-LYMPHOCYTE SERUM, ANTI-GAMMA GLOBULIN SERUM, SPECIFIC ANTIGEN, AND PHYTOHEMAGGLUTININ - Foerster, John (The Rockefeller University Press, 1969)
Rabbit anti-guinea pig lymphocyte serum is an efficient stimulus of the synthesis of DNA by guinea pig lymph node cells in vitro. The ability of ALS to stimulate lymphocytes is characterized by its lack of dependence on prior sensitization, the magnitude of the response it elicits, and the stimulation of all sensitive lymph node cells simultaneously within a very narrow range of ALS concentrations. In contrast to this homogeneous response to ALS, the stimulation of lymph node cells by antigen proceeds in graded fashion over a wide range of concentrations, thus reflecting the heterogeneity of the response of sensitized cells to antigen. PHA gives a response which is intermediate between that of ALS and antigen. ALS appears to have specificity for membrane determinants shared by lymphocytes but not found on other tissues. This specificity does not involve cell-bound gamma globulin. The serum activity mediating lymphocyte stimulation as well as cytotoxicity is readily removed by absorption with lymph node cells.